Exploring the Socio-Economic Factors that Affects the Classroom Performance of Students of Child Protection & Welfare Bureau in Gujranwala - Nayab, Sahrish; Ul Hassan, Khawaja Hisham; Akmal, Farhana (Pakistan Journal of Humanities and Social Sciences, 2023)
Socioeconomic factors affect us. Socioeconomics emphasizes economics and society. Socioeconomics considers economic and social forces. These factors affect how different social classes work together. Classroom performance includes program objectives, achievements, and goals. The CP&WB protects abandoned and destitute children from neglect, abuse, manipulation, and violence. This qualitative study examined how socio-economic factors affect Gujranwala child protection & welfare bureau students' classroom performance. The study used semi-structured interviews. Purposive sampling was used to interview male and female Gujranwala teachers. The methodology helped analyze socioeconomic data and understand how it affected student performance in class. The interviews yielded 19 themes, of which the researchers selected those relevant to the project: qualification, experience, values, street children, child labour, status, classroom performance, facilities, and improvement. The study found that socioeconomic statuses, such as shelter, food, income, education, and health facilities, have a significant impact on classroom performance. The government and policymakers could develop a mechanism to support and increase services to control issues by analyzing how socioeconomic factors affect classroom performance.